A potential role for glia‐derived extracellular matrix remodeling in postinjury epilepsy. Issue 9 (5th June 2016) - Kim, Soo Young; Porter, Brenda E.; Friedman, Alon; Kaufer, Daniela
Abstract : Head trauma and vascular injuries are known risk factors for acquired epilepsy. The sequence of events that lead from the initial injury to the development of epilepsy involves complex plastic changes and circuit rewiring. In‐depth, comprehensive understanding of the epileptogenic process is critical for the identification of disease‐modifying targets. Here we review the complex interactions of cellular and extracellular components that may promote epileptogenesis, with an emphasis on the role of astrocytes. Emerging evidence demonstrates that astrocytes promptly respond to brain damage and play a critical role in the development of postinjury epilepsy. Astrocytes have been shown to regulate extracellular matrix (ECM) remodeling, which can affect plasticity and stability of synapses and, in turn, contribute to the epileptogenic process. From these separate lines of evidence, we present a hypothesis suggesting a possible role for astrocyte‐regulated remodeling of ECM and perineuronal nets, a specialized ECM structure around fast‐spiking inhibitory interneurons, in the development and progression of posttraumatic epilepsies. © 2016 Wiley Periodicals, Inc.